2016
DOI: 10.1007/s12182-016-0090-9
|View full text |Cite
|
Sign up to set email alerts
|

CO2-triggered gelation for mobility control and channeling blocking during CO2 flooding processes

Abstract: CO 2 flooding is regarded as an important method for enhanced oil recovery (EOR) and greenhouse gas control. However, the heterogeneity prevalently distributed in reservoirs inhibits the performance of this technology. The sweep efficiency can be significantly reduced especially in the presence of ''thief zones''. Hence, gas channeling blocking and mobility control are important technical issues for the success of CO 2 injection. Normally, crosslinked gels have the potential to block gas channels, but the gela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 43 publications
0
26
0
Order By: Relevance
“…Normally, the capacity of the gel system for water shutoff or water shutoff efficiency can be evaluated by the reduction in permeability of the sand pack after the gel treatment (Chen et al 2015;Kang et al 2015;Karimi et al 2014;Li et al 2016;You et al 2015), which is defined as:…”
Section: Sand Pack Flooding Experimentsmentioning
confidence: 99%
“…Normally, the capacity of the gel system for water shutoff or water shutoff efficiency can be evaluated by the reduction in permeability of the sand pack after the gel treatment (Chen et al 2015;Kang et al 2015;Karimi et al 2014;Li et al 2016;You et al 2015), which is defined as:…”
Section: Sand Pack Flooding Experimentsmentioning
confidence: 99%
“…The responsive process is illustrated in Figure 6B. The responsivity tests showed that the tertiary amine groups could interact with CO 2 /N 2 , which could be used to control the properties of nanofluid such as in CO 2 -triggered switchable surfactants reported by Liang et al (2011), CO 2 -sensitive foams researched by Li et al (2016), or CO 2 -triggered gelation proposed by Li et al (2017). However, this paper intends to control the stability of nanoparticles in nanofluid via CO 2 /N 2 response.…”
Section: Co 2 /N 2 Responsementioning
confidence: 98%
“…The conventional methods utilized to mitigate CO 2 gas channeling are gel injection, polymer injection, and foam injection. Li et al (2016) proposed the modification of polyacrylamide-methenamine-resorcinol gel agents to block CO 2 channeling. Sun et al (2016) reported that aqueous foams stabilized by partially hydrophobic SiO 2 showed better CO 2 mobility control performance.…”
Section: Introductionmentioning
confidence: 99%
“…In the bottle test, the time of hydrogel formation (gelation time) is measured, while the hydrogel is not under stress or shear (Akhlaghi Amiri and Hamouda 2014;Salimi et al 2014). Generally, the bottle test is a simple and fast method to evaluate the gelation time, gel strength, heat resistance, syneresis time (Karimi et al 2016;Li et al 2016), and to determine the hydrogel composition of cross-linker and polymer (Adewunmi et al 2017). The samples were transferred into high thermal resistance glass tubes (70 mL, Simax, Italy) and were kept at 90°C in an UN55 oven (Memmert, Germany).…”
Section: Bottle Testsmentioning
confidence: 99%